Documentos curriculares, movimento humano e educa????o infantil: um estudo a partir da fala dos professores - Marco, Melissa Cecato de (2019)
The intensity that curricular reforms have been proposed transformed the educational field into a place where different educational and curriculum concepts are presented, defended and questioned. From the scope of this debate arises the object of this research: the curricular guidance documents for the Early Childhood Education of S??o Paulo district teaching system, specifically the approach given to corporal and movement expressions. The core issue, that guides this research could be defined as: what meanings do the corporal expressions and movement have in the S??o Paulo curricular documents of Early Childhood Education? This issue unfolds in a second question: how do the teachers understand these issues within their school practice? Firstly, our aim is to understand how the curricular documents define concepts as corporal references, gestures and movements. Next, is to verify how the child education teachers?? of S??o Paulo education network define their practices in relation to the documents. Our research sources consist of the following documents: the Curr??culo Integrador da Inf??ncia Paulistana (2015) produced by the S??o Paulo Municipal Education Department and the Base Nacional Comum Curricular (BRASIL/MEC, 2017), as well as semi-structured interviews with teachers of the municipal education system in S??o Paulo. The semi-structured interviews with teachers were analyzed through the content analysis proposed by Bardin (1995). The analysis of Curriculum Integrator showed that it presents approximations with the cultural studies theoretical perspectives. The interviews indicate that the teachers know and use the guiding documents, and that they perform study collective actions and educational planning. Nevertheless, they mention difficulties related to the pedagogical practices effectiveness, due to the presumable barrier of understanding that they present related to the documents curricular orientation??s theoretical assumptions, especially in the field of movement.